Proceedings of the 2015 New Security Paradigms Workshop 2015
DOI: 10.1145/2841113.2841118
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Contribution of Critical Visualisation to Information Security

Abstract: This paper examines the use of visualisations in the field of information security and in particular focuses on the practice of information security risk assessment. We examine the current roles of information security visualisations and place these roles in the wider information visualisation discourse. We present an analytic lens which divides visualisations into three categories: journalistic, scientific and critical visualisations. We then present a case study that uses these three categories of visualisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…While our focus was on ASD, we felt that our results could be more broadly applicable. Our use of RPs to augment a traditional focus group discussion was motivated by similar approaches for novel user engagements to better understand their security and privacy needs [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…While our focus was on ASD, we felt that our results could be more broadly applicable. Our use of RPs to augment a traditional focus group discussion was motivated by similar approaches for novel user engagements to better understand their security and privacy needs [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…There is a profound requirement to handle complexity and qualitative space in the social sciences and digital humanities. The 'field inscription' approach described in the previous section has shown that it can be adapted to the analysis and representation of participatory research data (Figure 6) [23], and has the potential to support critical approaches [24]. It can also help develop visual analysis tools in ethnomethodology [25].…”
Section: Discussionmentioning
confidence: 99%
“…We have published key innovations in for example the attack navigation metaphor [14], making attacker profiles explicit [28], attack generation [20,21], quantitative analysis [29,30], and visualisation of maps and paths [31,32]. Our practical and theoretical developments open up for many new and interesting research questions in the area of attack navigation and graphical models for security, for example:…”
Section: Discussionmentioning
confidence: 99%